The Joy Luck Club - Tan, Amy. (New York : Penguin Books, 2006)
The personal, often painful, histories of four Chinese American women who began meeting in San Francisco in 1949 to play mah jong are revealed as the daughter of one who has died searches for her sisters in China to tell them about the mother they never knew.
Notable/Best Books (A.L.A.).
Wilson's Fiction.
Wilson's Senior High School.
Young Adult
Keywords: Chinese Americans -- Fiction; Mothers and daughters -- United States -- Fiction; Chinese Americans -- Fiction; Domestic fiction; Mother-daughter relationship -- Fiction